2011
DOI: 10.3892/mmr.2011.469
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the ratio of T-bet/GATA-3 and the levels of IL-4 and IFN-γ in patients with allergic asthma

Abstract: Abstract. The aim of this study was to investigate the ratio of the transcription factors T-bet/GATA-3 in patients with allergic asthma. Forty-seven individuals with allergic asthma and 47 healthy control individuals provided 5 ml of anticoagulated peripheral venous blood. Lymphocytes in peripheral blood were isolated by Ficoll and treated with phytohemagglutinin (PHA) at a final concentration of 100 mg/l for 48 h. Interferon-γ (IFN-γ) and interleukin-4 (IL-4) levels were detected using an enzyme-linked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Since naïve CD4 + T cells from SMAR1 −/− mice have impaired Th2 differentiation in the lung, allergic inflammation leads to aberrant expression of genes that are responsible for Th1 and Th17 commitment, which in turn suppresses Th2 response in vivo . This observation is in line with the previous reports suggesting the elevated T-bet expression in SMAR1 −/− mice after chronic allergic antigen exposure ( 41 , 71 , 73 ). It shows SMAR1 is a novel and essential factor for the establishment of Th2 cells by functioning as a Th1-specific transcriptional gene repressor.…”
Section: Nuclear Matrix-binding Protein Smar1: Essential Regulator Ofsupporting
confidence: 93%
“…Since naïve CD4 + T cells from SMAR1 −/− mice have impaired Th2 differentiation in the lung, allergic inflammation leads to aberrant expression of genes that are responsible for Th1 and Th17 commitment, which in turn suppresses Th2 response in vivo . This observation is in line with the previous reports suggesting the elevated T-bet expression in SMAR1 −/− mice after chronic allergic antigen exposure ( 41 , 71 , 73 ). It shows SMAR1 is a novel and essential factor for the establishment of Th2 cells by functioning as a Th1-specific transcriptional gene repressor.…”
Section: Nuclear Matrix-binding Protein Smar1: Essential Regulator Ofsupporting
confidence: 93%
“…A previous studied showed that the mRNA expression levels of T-bet and IFN-γ were lower, whereas the mRNA expression levels of GATA-3 and IL-4 were higher in the nasal mucosa of AR mice compared with those of normal mice, thus inhibiting the Th1 immune response and enhancing the Th2 immune response, respectively (40). The mRNA imbalance of T-bet/GATA-3 and IFN-γ/IL-4 results in an imbalance of the Thl/Th2 immune response (4,41), which leads to the occurrence of AR. Enhancing the Th1 and/or reducing the Th2 immune response to correct the Thl/Th2 imbalance may prevent allergic inflammatory reactions and ease the symptoms of allergic diseases (23,5,13–15).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the preclinical safety evaluation of drugs, allergic reaction is among the most difficult factors to predict due to the lack of appropriate models for predicting clinical allergic reactions (15). The establishment of appropriate animal models for allergic reaction prediction, and their successful application to predicting drug allergies are required (16,17). The present results demonstrated that Artemisia extract pretreatment is capable of reducing the systemic anaphylactic shock, histamine release, scratching behavior and vascular permeability induced by compound 48/80.…”
Section: Discussionmentioning
confidence: 65%